Reversible electric control adsorption device
By using electrodeformed polyvinyl chloride dielectric gel adsorption layer and conductive copper mesh anode in the suction cup device, combined with the pre-oxidized eutectic gallium indium alloy cathode layer, efficient electronically controlled adsorption and desorption are achieved, solving the traditional suction cup The device is bulky, poor flexibility and insufficient adsorption capacity, providing flexible and precise adsorption solutions.
Patent Information
- Application Number
- CN202411523110.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Traditional suction cup devices have problems such as bulky size, poor flexibility, difficulty in miniaturization and insufficient adsorption during object transportation. In particular, vacuum suction cups require air pumps, magnetic suction cups are complex and limited in assembly, and insufficient adsorption force of electrostatic suction cups.
A reversible electrically controlled adsorption device is designed, using a polyvinyl chloride dielectric gel adsorption layer with electrodeformation characteristics and a conductive copper mesh anode, combined with a pre-oxidized eutectic gallium indium alloy cathode layer, and the adsorption layer is deformed by electric field induced. Adsorption and desorption ensure the enclosure and stability of the adsorption chamber.
It realizes adsorption operation with strong adsorption force, simple structure, fast response speed and high control accuracy, and can quickly and reversibly adsorb and release objects, and is suitable for a variety of application scenarios.
Smart Images

Figure CN119115999A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of industrial suction cups, and in particular to a reversible electrically controlled adsorption device based on polyvinyl chloride dielectric gel. Background Art
[0002] In the fields of robotics, industrial automation, aerospace, etc., end effectors are usually used to transport objects. In order to solve the problem that traditional rigid manipulators / claws cause great damage to the target objects, people have designed a variety of suction cup devices to grasp large-format objects, and achieved good results.
[0003] At present, common adsorption end grippers include pneumatic suction cups, magnetic suction cups, electrostatic suction cups, etc. For example, the vacuum suction cup has a simple structure, but it is driven by vacuum negative pressure and requires an air pump. It has problems such as bulky size, poor flexibility, and difficulty in miniaturization. Another example is the magnetic suction cup, which uses magnetic response materials and external magnetic fields to achieve adsorption and desorption. Although it can provide good adsorption performance, the assembly equipment required for the magnetic control suction cup is complicated and cumbersome, and requires a relatively bulky electromagnetic generator, which has great limitations in actual use. The electrostatic suction cup is based on the principle of electrostatic adsorption and requires the surface of the adsorbed object to have conductive properties, but the adsorption force generated by this suction cup is very small and insufficient to meet the adsorption requirements. Summary of the invention
[0004] The present invention aims to provide a reversible electrically controlled adsorption device with strong adsorption force and simple structure.
[0005] In order to solve the above problems, the present invention provides a reversible electrically-controlled adsorption device, including a cover body, wherein the upper end of the cover body is an upper cover, and the lower end is a cover opening, an anode is arranged on the circumference of the inner wall of the cover body, and the cover opening is closed by a layer of adsorption layer with electro-deformation, and the cover body upper cover, the inner wall of the cover body and the inner side of the adsorption layer together form an adsorption cavity; a cathode layer that can deform with the adsorption layer is arranged on the outer surface of the adsorption layer, and a sealing ring is arranged on the outer side of the adsorption layer along the edge of the cover opening.
[0006] Beneficial effects: (1) The present invention uses an adsorption layer with electrodeformation properties as a key component. When the device is in close contact with the surface of the target object, the adsorption layer, the cover mouth and the surface of the target object form a sealed space. The adsorption layer can undergo significant volume changes or shape deformations under the action of the electric field. When voltage is applied, an electric field is formed between the anode and the cathode. The electric field induces the negatively charged substances in the adsorption layer to migrate toward the positively charged anode, forming a negative charge enrichment layer close to the anode side, and attracting the anode, thereby driving the adsorption layer to creep deform along the anode on the cover wall (that is, the adsorption layer is concave into the adsorption cavity). Therefore, the volume of the adsorption cavity is reduced, and the sealed space is increased to generate negative pressure, thereby achieving adsorption of the target object. After power failure, the adsorption layer can quickly return to its initial state, thereby separating the cover from the target object. This electrically controlled adsorption effect not only has a fast response speed, but also has high control accuracy, and can achieve fast and reversible adsorption operations;
[0007] (2) The present invention provides a sealing ring along the edge of the cover on the outside of the adsorption layer. The sealing ring is closely matched with the adsorption layer to effectively prevent interference from the external environment and leakage of internal gas. This design ensures the closure and stability of the adsorption chamber during operation and improves the adsorption efficiency.
[0008] (3) The present invention can accurately control the deformation degree of the adsorption layer and thus the volume change of the adsorption chamber by adjusting the voltage and polarity applied to the electrode plate. This reversible control method makes the device have great application value in situations where the adsorbed material needs to be frequently replaced or released.
[0009] The invention achieves precise control of the adsorption process by ingeniously combining the electrodeformable material with the electric field, can adjust the adsorption force and has a simple structure, and has significant technical effects and broad application prospects.
[0010] Furthermore, the adsorption layer is a layered structure made of polyvinyl chloride dielectric gel, and a pre-oxidized eutectic gallium-indium alloy layer is coated on the outer side as a cathode layer; the anode is a cylindrical structure made of a conductive copper mesh.
[0011] Under the action of the electric field, the small molecules of dibutyl adipate in the polyvinyl chloride dielectric gel migrate toward the anode, forming a negative charge enrichment layer near the anode side, thereby causing the adsorption layer to deform toward the anode (that is, the adsorption layer is concave toward the adsorption cavity), thereby achieving more efficient adsorption; the anode is a cylindrical structure made of a conductive copper mesh, which not only has excellent conductivity, can ensure that the electric field is evenly distributed and effectively transmitted to the polyvinyl chloride dielectric gel layer, but also its mesh structure provides good mechanical support and flexibility, the adsorption layer can be close to the anode during deformation, making its concave deformation more stable and reliable; and the pre-oxidized eutectic gallium-indium alloy is used as the cathode layer. This alloy has the characteristics of easy stretching (modulus is almost zero), low resistance and stability (resistance change is almost zero when stretched), especially after pre-oxidation treatment, the coatability and bonding stability with the surface of the polyvinyl chloride dielectric gel are improved, so that the cathode electrode can deform adaptively with the deformation of the adsorption layer, further improving the adsorption efficiency.
[0012] Furthermore, the sealing ring is a polyvinyl chloride dielectric gel ring, and is bonded to the edge of the cover opening by polyvinyl chloride dielectric gel liquid, so that the sealing ring and the cover opening are fastened.
[0013] Furthermore, the mass fractions of the polyvinyl chloride dielectric gel are as follows:
[0014] 1 part of polyvinyl chloride polymer;
[0015] 1-15 parts of dibutyl adipate;
[0016] 10 to 30 parts of tetrahydrofuran.
[0017] Furthermore, the mass proportions of the polyvinyl chloride dielectric gel are: 1 part of polyvinyl chloride polymer, 6 parts of dibutyl adipate, and 15 parts of tetrahydrofuran. The polyvinyl chloride dielectric gel under this ratio has a small modulus and a large dielectric constant; or 1 part of polyvinyl chloride polymer, 1 part of dibutyl adipate, and 10 parts of tetrahydrofuran. The polyvinyl chloride dielectric gel under this ratio has a large modulus, a small dielectric loss, and is resistant to breakdown; or 1 part of polyvinyl chloride polymer, 15 parts of dibutyl adipate, and 30 parts of tetrahydrofuran. The polyvinyl chloride dielectric gel under this ratio has a small modulus and a strong deformation ability.
[0018] Furthermore, the pre-oxidized eutectic gallium-indium liquid alloy layer is formed by stirring the eutectic gallium-indium liquid alloy, introducing air to oxidize the gallium metal (generating an oxidant) to obtain a paste, and then coating the paste on the surface of the adsorption layer. The presence of gallium oxide converts the easy-flowing eutectic gallium-indium liquid alloy into a highly stable paste, so that the cathode layer formed in this way not only has high conductivity and negligible additional stiffness, but also has good electrical stability during cyclic driving.
[0019] Furthermore, the cover body is a conical cover that is narrow at the top and wide at the bottom, and the anode is a conical mesh cover that is narrow at the top and wide at the bottom, so that the anode can be supported by the conical mesh cover during the deformation process.
[0020] Furthermore, the lower end of the anode contacts the adsorption layer, so that the distance between the anode and the cathode layer is smaller, and the electric field strength formed between the two is greater when the potential difference remains unchanged. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the three-dimensional structure of a reversible electric-controlled adsorption device embodiment 1 of the present invention;
[0022] Figure 2 It is a schematic diagram of the three-dimensional structure of a reversible electric-controlled adsorption device embodiment 1 of the present invention;
[0023] Figure 3 This is an adsorption principle diagram of Example 1 of a reversible electrically controlled adsorption device of the present invention;
[0024] Figure 4 The strain-resistance change curve obtained from the stretching-conductivity performance experiment;
[0025] Figure 5 This is the elastic modulus diagram obtained from the tensile-conductive performance experiment;
[0026] Figure 6 This is a stroke-adsorption force diagram of the reversible electrically controlled adsorption device corresponding to Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The reference numerals in the drawings of the specification include: an upper cover 1, a conical mesh cover 2, a first wire 3, an adsorption layer 4, a sealing ring 5, and a second wire 6.
[0028] (I) Embodiment 1
[0029] like Figure 1-Figure 3 As shown, a reversible electric-controlled adsorption device of the present invention comprises a cover body which is narrow at the top and wide at the bottom and is conical, wherein the upper end is a closed upper cover 1 with a through hole, and the lower end is an open cover opening.
[0030] The inner wall of the cover is provided with a conical mesh cover 2 made of conductive copper wire, which is narrow at the top and wide at the bottom. The conical mesh cover 2 is an anode and is connected to a first wire 3. The first wire 3 passes through the through hole and is connected to the positive electrode of the power supply.
[0031] The cover opening is closed by an adsorption layer 4 made of polyvinyl chloride dielectric gel, and the cover upper cover 1, the cover inner wall and the inner side of the adsorption layer 4 together form an adsorption cavity.
[0032] The outer side of the adsorption layer 4 is coated with a pre-oxidized eutectic gallium-indium alloy as a cathode layer, and a sealing ring 5 is bonded to the outer side of the adsorption layer 4 along the edge of the cover through a polyvinyl chloride dielectric gel liquid. The sealing ring 5 is an annular ring made of polyvinyl chloride dielectric gel. The cathode layer is soldered to the second conductive wire 6, and the second conductive wire 6 passes through the sealing ring and is connected to the negative electrode of the power supply. Since the sealing ring 5 has a certain thickness, when the reversible electrically controlled adsorption device contacts the surface of the target object, a sealed space is formed between the adsorption layer 4 and the target object.
[0033] The ratio and preparation method of the polyvinyl chloride dielectric gel and the pre-oxidized eutectic gallium-indium alloy in this embodiment 1 are as follows:
[0034] Polyvinyl chloride dielectric gel: The mass proportions of the raw materials are polyvinyl chloride polymer: dibutyl adipate: tetrahydrofuran = 1:6:15. The raw materials are blended and stirred evenly to obtain a polyvinyl chloride dielectric gel stock solution, which is then poured into a corresponding mold. After the tetrahydrofuran evaporates, the adsorption layer 4 and the sealing ring 5 can be obtained.
[0035] Pre-oxidized eutectic gallium-indium alloy: the mass fraction of the liquid alloy raw material is gallium:indium=75:25. The eutectic gallium-indium liquid alloy is stirred for 60 minutes using a magnetic stirrer to form a paste, which is then coated on the outside of the adsorption layer 5.
[0036] like Figure 3 As shown, after power is turned on, under the action of the electric field, the small molecules of dibutyl adipate in the adsorption layer 5 (polyvinyl chloride dielectric gel) migrate toward the anode, forming a negative charge enrichment layer near the anode side, which in turn causes the adsorption layer to deform toward the anode (i.e., the adsorption layer 5 is sunken into the adsorption cavity), thereby achieving adsorption; after power is turned off, the electric field disappears, the adsorption layer 5 returns to its original position, and desorption is achieved.
[0037] (II) Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3
[0038] The structures, adsorption layer materials, and cathode materials of Example 2 and Example 3 are the same as those of Example 1, but the specific ratios and preparation methods are different. The structures of Comparative Examples 1, Comparative Examples 2, and Comparative Examples 3 are the same as those of Example 1, but the materials / preparation methods of the adsorption layer and cathode are different. The specific details are shown in the following table:
[0039]
[0040]
[0041] (III) Performance test
[0042] (1) Elastic modulus test of adsorption layer
[0043] The adsorption layers in Examples 1 to 6 were cut to the same specifications (length 10 mm×width 10 mm), and were stretched at a uniform speed using a universal testing machine, and stress-strain curves were calculated and plotted, wherein the calculation method of stress and strain is as follows:
[0044] Stress (σ): refers to the force per unit area, calculated by the formula σ=F / A, where F is the force acting on the material and A is the contact area of the force. It describes the intensity of the external force on the material.
[0045] Strain (ε): refers to the relative deformation of a material when it is subjected to an external force. The calculation formula is ε = ΔL / L, where ΔL is the deformation of the material in the direction of the force and L is the original length of the material. It describes the degree of deformation of the material under the action of an external force.
[0046] The elastic modulus is obtained by calculating the slope of the 0-10% interval of the stress-strain curve as shown in the following table:
[0047] Elastic modulus of adsorption layer (kPa) Example 1 0.077MPa Example 2 0.423MPa Example 3 0.039MPa Comparative Example 1 0.169MPa Comparative Example 2 0.077MPa Comparative Example 3 0.077MPa
[0048] Note: Example 1, Comparative Example 2 and Comparative Example 3 use exactly the same polyvinyl chloride dielectric gel, so the experimental results are completely consistent.
[0049] It can be seen from the above table that the elastic modulus is: Example 2>Comparative Example 1>Example 1=Comparative Example 2=Comparative Example 3>Example 3. In theory, the larger the elastic modulus, the harder it is to deform and the smaller the adsorption force, which will be further verified in subsequent performance tests.
[0050] (2) Tensile-conductive properties test
[0051] The adsorption layer in Example 1 was selected as a reference sample, the adsorption layer prepared in Example 1 (coated with the cathode layer in Example 1) was selected as Sample 1, and the adsorption layer prepared in Comparative Example 3 (coated with the cathode layer in Comparative Example 3) was selected as Sample 2.
[0052] At room temperature, use a universal tensile testing machine to stretch sample 1 and sample 2 (both with a length of 10 mm and a width of 10 mm). Paste conductive tape on both ends and connect wires to a digital source meter. Use a digital source meter to test the resistance during the stretching process. Record: (1) Record data every 10% of strain, including the stretching and recovery stages, and draw a strain-resistance curve. Figure 4 , the resistance of sample 1 and sample 2 can be obtained as a function of tensile strain; (2) during stretching, the stress-strain curve is plotted to obtain the elastic modulus of sample 1 and sample 2, which is plotted together with the elasticity of the reference sample into an elastic modulus graph. The results are shown in Figure 5 .
[0053] Depend on Figure 4It can be seen that the resistance of sample 1 (coated with pre-oxidized eutectic gallium-indium alloy) changes very little under 100% strain, and the resistance curves of the recovery process and the stretching process almost coincide, indicating that its resistance is stable and not easily disturbed by external deformation. The resistance of sample 2 (coated with carbon paste) changes significantly under 100% strain, and the resistance curves of the recovery process and the stretching process do not coincide. The tensile deformation causes the resistance of the carbon paste electrode to change, and its tensile resistance is poor, which is easily affected by external deformation.
[0054] Depend on Figure 5 It can be seen that the elastic modulus of sample 1 increased by 0.044 MPa compared with the reference sample (not coated with any material), and that of sample 2 increased by 0.095 MPa compared with the reference sample, indicating that after the pre-oxidized eutectic gallium-indium alloy was coated with polyvinyl chloride dielectric gel, its modulus increased less, while the modulus increased more after coating with carbon paste.
[0055] In summary, the pre-oxidized eutectic gallium-indium alloy has stable electrical properties and extremely low added modulus. It is superior to carbon paste when coated on polyvinyl chloride dielectric gel as an electrode, ensuring that the polyvinyl chloride dielectric gel layer can maintain stable adsorption performance during the self-adaptation process along the anode.
[0056] (3) Conductivity test
[0057] The adsorption layer coated with the eutectic gallium-indium liquid alloy was cut (length 10 mm×width 10 mm), and the resistance of the eutectic gallium-indium liquid alloy (cathode layer) was tested using a digital source meter, and the conductivity was calculated.
[0058] The conductivity (ρ) calculation formula is: ρ = RL / S, where R is the resistance, in Ω; L is the length of the eutectic gallium-indium liquid alloy, in mm; S is the cross-sectional area of the eutectic gallium-indium liquid alloy, in mm 2 The test results are shown in the following table:
[0059] sample Conductivity of pre-oxidized eutectic gallium-indium alloy (unit: S / m) Example 1 <![CDATA[3.09×10 6 ]]> Example 2 <![CDATA[3.17×10 6 ]]> Example 3 <![CDATA[3.20×10 6 ]]> Comparative Example 1 <![CDATA[3.09×10 6 ]]> Comparative Example 2 <![CDATA[3.23×10 6 ]]>
[0060] Note: Example 1 and Comparative Example 1 use exactly the same pre-oxidized eutectic gallium-indium liquid alloy, so the experimental results are completely consistent.
[0061] As can be seen from the above table, the conductivity results are Example 1 / Comparative Example 1> Example 2> Example 3. The reason is that the pre-oxidation time of the eutectic gallium-indium alloy in Example 1, Example 2, and Example 3 is 60 minutes, 40 minutes, and 20 minutes, respectively. As the stirring time decreases, the non-conductive gallium oxide content is low, and the conductivity is stronger, so the conductivity is higher. Comparative Example 1 uses the same pre-oxidation eutectic gallium-indium alloy stirred for 60 minutes as Example 1, and the conductivity is consistent with Example 1.
[0062] Comparative Example 2 uses a eutectic gallium-indium alloy without any mechanical stirring, which has the highest conductivity. However, combined with the subsequent performance test results, it is found that the adsorption force of Comparative Example 2 is 0, indicating that the eutectic gallium-indium alloy without pre-oxidation cannot form an electrode layer on the surface due to insufficient viscosity, and therefore cannot be used. On the other hand, from the comparison of the absolute values of the conductivity of the samples, it can be seen that although stirring will reduce the conductivity, the actual decrease is also very limited. Even the difference between Example 1 with the longest stirring time and Comparative Example 2 without stirring is only 0.14×10 6 .
[0063] 2. Adsorption performance test
[0064] The adsorption formation experiment of Example 1 was carried out under a voltage of 0-900V. The test method was as follows: the upper cover of the cover body was fixed to the upper clamp of the universal tensile testing machine, and a glass plate was horizontally fixed at the lower clamp as the target adsorbent. After power was turned on, the universal tensile testing machine was used to pull up at a uniform speed and measure the adsorption force. Figure 6 As shown, the adsorption force is different under different voltages, and the adsorption force gradually increases with the increase of voltage. Among them, at the maximum voltage of 900V, the adsorption force can reach 0.46MPa, which is about the weight of 4 eggs or a middle school textbook. It shows that the adsorption force of the suction cup meets the adsorption needs in production and life; after exceeding 900V, the electric field is broken down, and the maximum adsorption force is reached at this time. Therefore, the voltage upper limit should be controlled when using it.
[0065] Continue to assemble Implementations 2 to 3 and Comparative Examples 1 to 3 into corresponding reversible electrically controlled adsorption devices in the same manner, and measure their maximum adsorption forces. The test results are summarized in the following table:
[0066] Maximum adsorption force (unit: MPa) Example 1 0.46MPa Example 2 0.33MPa Example 3 0.12MPa Comparative Example 1 0 Comparative Example 2 0 Comparative Example 3 The cathode is disconnected due to external pressure, the conductivity is unstable and cannot be measured.
[0067] As can be seen from the above table, Examples 1, 2, and 3 all use polyvinyl chloride dielectric gel as the adsorption layer and pre-oxidized eutectic gallium-indium alloy as the cathode, and their adsorption force is significant. The three examples show different adsorption forces due to different ratios, Example 1> Example 2> Example 3. Combined with material experiments, it can be seen that the adsorption layer used in Example 1 has a low elastic modulus and is easy to adsorb, so the adsorption force is the largest; the adsorption layer used in Example 2 has a large elastic modulus and is difficult to deform, so the adsorption force is lower than that of Example 1; the adsorption layer used in Example 3 has the lowest elastic modulus, but the polyvinyl chloride polymer content in the adsorption layer is low, and thus the overall dielectric constant of the material is small, which makes it easy to be broken down, and the maximum adsorption force is the smallest.
[0068] Comparative Example 1 uses silica gel as the adsorption layer, which has no adsorption effect and thus has no adsorption force. Comparative Example 2 uses eutectic gallium-indium alloy without any mechanical stirring. Due to insufficient viscosity, an electrode layer cannot be formed on the surface of the adsorption layer, so it cannot be used as an electrode. Comparative Example 3 uses carbon paste coating, which is prone to short circuit and cannot be measured.
[0069] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by the present invention shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A reversible electrically controlled adsorption device, comprising a cover body, wherein the upper end of the cover body is an upper cover and the lower end is a cover opening, characterized in that: An anode is arranged on the circumference of the inner wall of the cover body, the cover opening is closed by an adsorption layer with electro-deformation, and the cover upper cover, the inner wall of the cover body and the inner side of the adsorption layer together form an adsorption cavity; a cathode layer which can be deformed with the adsorption layer is arranged on the outer surface of the adsorption layer, and a sealing ring is arranged along the edge of the cover opening on the outside of the adsorption layer.
2. A reversible electrically controlled adsorption device according to claim 1, characterized in that: The adsorption layer is a layered structure made of polyvinyl chloride dielectric gel, and the outer side of the adsorption layer is coated with a pre-oxidized eutectic gallium-indium alloy layer as a cathode layer; the anode is a cylindrical structure made of a conductive copper mesh.
3. A reversible electrically controlled adsorption device according to claim 2, characterized in that: The sealing ring is a polyvinyl chloride dielectric gel ring and is bonded to the edge of the cover opening by polyvinyl chloride dielectric gel liquid.
4. A reversible electrically controlled adsorption device according to claim 3, characterized in that: The mass fractions of the polyvinyl chloride dielectric gel are as follows: 1 part of polyvinyl chloride polymer; 1-15 parts of dibutyl adipate; 10 to 30 parts of tetrahydrofuran.
5. A reversible electrically controlled adsorption device according to claim 4, characterized in that: The mass fractions of the polyvinyl chloride dielectric gel are as follows: 1 part of polyvinyl chloride polymer; 6 parts of dibutyl adipate; 15 parts of tetrahydrofuran.
6. A reversible electrically controlled adsorption device according to claim 4, characterized in that: The mass fractions of the polyvinyl chloride dielectric gel are as follows: 1 part of polyvinyl chloride polymer; 1 part of dibutyl adipate; 10 parts of tetrahydrofuran.
7. A reversible electrically controlled adsorption device according to claim 4, characterized in that: The mass fractions of the polyvinyl chloride dielectric gel are as follows: 1 part of polyvinyl chloride polymer; 15 parts of dibutyl adipate; 30 parts of tetrahydrofuran.
8. A reversible electrically controlled adsorption device according to claim 5, 6 or 7, characterized in that: The pre-oxidized eutectic gallium-indium liquid alloy layer is formed by stirring the eutectic gallium-indium liquid alloy, introducing air to oxidize the gallium metal to obtain a paste, and then coating the paste on the surface of the adsorption layer.
9. A reversible electrically controlled adsorption device according to claim 8, characterized in that: The cover body is a conical cover which is narrow at the top and wide at the bottom, and the anode is a conical cylinder mesh cover which is narrow at the top and wide at the bottom.
10. A reversible electrically controlled adsorption device according to claim 9, characterized in that: The lower end of the anode contacts the adsorption layer.
Citation Information
Patent Citations
Plane sucker, conveying equipment and medical robot
CN112025674A
Double-sided adsorption electrostatic chuck and assembly structure thereof
CN113571460A
Adsorption device based on magnetic force type dielectric elastomer driver
CN115744287A
Electrostatic chuck
JP2000106392A
Active material based suction cups
US20080078896A1
